Reports of Adverse Events Associated with Use of Novel Psychoactive Substances, 2013–2016: A Review - Logan, Barry K.; Mohr, Amanda L.A.; Friscia, Melissa; Krotulski, Alex J.; Papsun, Donna M.; Kacinko, Sherri L.; Ropero-Miller, Jeri D.; Huestis, Marilyn A. (Journal of analytical toxicology, 2017)
Abstract Novel psychoactive substances (NPS) represent significant analytical and interpretive challenges to forensic and clinical toxicologists. Timely access to case reports and reports of adverse incidents of impairment or toxicity is imperative to clinical diagnosis and treatment, as well as to interpretation of forensic results. Delays in identifying the presence of a novel intoxicating agent have significant consequences for public health and public safety. Adverse effects of intoxications with novel cannabinoids, stimulants, hallucinogens, benzodiazepines and opioids spanning January 2013 through December 2016 as reported in emergency departments, death investigations, impaired driving cases and other forensic contexts are the subject of this review. Discussion of the chemistry, pharmacology and adverse events associated with novel drug classes is summarized and described within. Adverse effects or symptoms associated with ingestion of more than 45 NPS have been abstracted and summarized in tables, including demographics, case history, clinical or behavioral symptoms, autopsy findings and drug confirmations with quantitative results when provided. Based on these findings and gaps in the available data, we provide recommendations for future toxicological testing of these evolving substances. These include development and management of a national monitoring program to provide real-time clinical and toxicological data, confirmed analytically, on emerging drugs and their known toxidromes and side effect profiles. Increased efforts should be made to analytically confirm the agents responsible for clinical intoxications involving adverse events in emergency department admissions or hospitalizations. Evidence-based community preparedness among analytical laboratories gained through active communication and sharing of toxicological findings and trends in NPS is imperative to assist in enabling early detection of new drugs in forensic and clinical populations.